Predominant Dissemination of PVL-Negative CC89 MRSA with SCCmec Type II in Children with Impetigo in Japan - H. Kikuta; M. Shibata; S. Nakata; T. Yamanaka; H. Sakata; K. Akizawa; K. Kobayashi (International Journal of Pediatrics)
Background. The ratio of CA-MRSA in children with impetigo has been increasing in Japan. Methods. Antimicrobial susceptibilities of 136 S. aureus isolates from children with impetigo were studied. Furthermore, molecular epidemiological analysis and virulence gene analysis were performed. Results. Of the 136 S. aureus isolates, 122 (89.7%) were MSSA and 14 (10.3%) were MRSA. Of the 14 MRSA strains, 11 belonged to CC89 (ST89, ST91, and ST2117) and carried diverse types of SCCmec: type II (IIb: 3 strains; unknown subtype: 4 strains), type IVa (2 strains), and unknown type (2 strains). The remaining three strains exhibited CC8 (ST-8)-SCCmec type VIa, CC121 (ST121)-SCCmec type V, and CC5 (ST5)-nontypeable SCCmec element, respectively. None were lukS-PV-lukF-PV gene positive. Gentamicin- and clarithromycin-resistant strains were frequently found in both MRSA and MSSA. Conclusions. PVL-negative CC89-SCCmec type II strains are the most predominant strains among the CA-MRSA strains circulating in the community in Japan.